Demographic-developmental distribution's imbalance in Al-jazeera region in Syria "General characteristics, and present and future effects" - Shuraiki, Mada; Al-kurdi, Hiba (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This paper discusses the social and economic development reality in Al-jazeera region in Syria, considering it as an essential economic area in the country. In fact, this region is the principal source of energy (oil and gas), and it is the first source of strategic agricultural and industrial crops (wheat and cotton). This economic reality was accompanied with a low level of social development (on both branches: education and hhealth) and with high levels of population growth rates; so that it presents one of the most expressive examples of the imbalance in the demographic-developmental distribution in Syria. The paper aims to describe the reality in Al-jazeera region, through descriptive-analytic study based on the most important data which provide a general vision concerning the economic production, the population growth and the health and educational advancement. It also tries to highlight the most important effects of this imbalanced distribution, especially the rural exodus towards the slims of major cities, where people work in marginal activities and suffer from low levels of educational and health services, which would leave a double negative effect that could be seen in both rustic and urban deformations.